Causes of Melena and Effective Examination Strategies in Children - Iwama, Itaru; Yoshida, Masashi; Hara, Tomoko; Nambu, Ryusuke (Frontiers in Pediatrics, 2021)
Background and aim Melena, or tarry black stool, is not a rare symptom encountered in pediatric clinical practice, and the bleeding source varies from the upper gastrointestinal tract to the small intestine. Endoscopy is effective in identifying bleeding, but it does not always identify the source of bleeding. Endoscopic examination in children is commonly challenging, and there are no detailed reports about the causes of melena in children. This observational study aimed to validate the cause of melena in children and to investigate more effective and less burdensome examination methods. Methods We retrospectively reviewed the clinical records of 55 patients who underwent examination for melena. Results In this research, 38 patients had underlying diseases such as malignancy and severe mental and physical disorders. The bleeding source was identified in 39 patients. The most common final diagnosis was duodenal ulcer (n = 22), and the other diagnoses were gastric ulcer, esophagitis, and esophageal varices. The upper gastrointestinal tract was the most common source of bleeding (n = 34). In five patients, the bleeding source was the small intestine. Vomiting, abnormal abdominal ultrasonography findings, and a hemoglobin level of ≤ 3 g/dL than the lower normal limit were significant factors indicating that the bleeding source can be found on esophagogastroduodenoscopy. Conclusions The upper gastrointestinal tract was the most common bleeding source of melena in children. As in adults, esophagogastroduodenoscopy is the primary endoscopic method of choice. Furthermore, small bowel capsule endoscopy may be useful in identifying the bleeding source in children without upper gastrointestinal lesions.